Validation of margins from setup errors in head and neck radiotherapy - Van der Merwe, Leandi (My University, 2017)
Aim: The aim of this study was to quantify random and systematic setup errors in a population of head and neck cancer patients for the purposes of evaluating departmental positioning and immobilization techniques, verification and treatment protocols, as well as validating the treatment margins used. Methods and Materials: All patients had more than one phase of radiation, each consisting of different megavoltage photon field arrangements. Some phases were also treated with electron fields in addition to the photon fields. Random and systematic setup errors in all three principal directions were calculated for two groups of patients, using record and verify system couch position data. For one group (20 patients) the positioning and immobilization device system was mechanically localized to the treatment couch, and for the other group (38 patients), it was visually centered on the treatment couch. Within both groups of patients, the patient position was either verified online with portal imaging or verified offline on a conventional radiotherapy simulator. Results: For the patient group treated with the base plate visually centered on the treatment table the population random and systematic setup errors calculated for the photon fields were only indicative of setup uncertainties in the anterior-posterior direction. For the patient group treated with the base plate localized to the treatment couch, the population random and systematic setup errors were found to be within the 5 mm clinical to planning target volume expansion margin used at Livingstone Hospital. Due to treatment couch position differences from fraction to fraction, setup errors made during this study could not reliably be determined for electron field treatments Conclusions: Results indicate that the base plate should be localized to the treatment couch when calculating random and systematic setup errors for photon fields using the couch position as a surrogate for patient position. For this method to be used to calculate setup errors for electron fields, shielding should always be fastened to the same position at the endface of the applicator. Offline and online verification did not significantly influence systematic setup errors.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science, 2017
Keywords: Head--Cancer--Treatment; Neck--Cancer--Treatment; Cancer--Radiotherapy